The relationship of ethical elements and work performance in the civil service : a study of support group staffs at Penang Regional Development Authority (PERDA) / Muhammad Syahmizan Azmi - Azmi, Muhammad Syahmizan (2013)
INTRODUCTION. Based on Vision 2020, Malaysia targeted to be a developed nation by the year 2020. The fourth challenge of the vision being mentioned was to build up the society with moral and ethical values embedded with strong religious belief and a sense of spirituality. Public sector therefore has been recognized as the main engine in realizing the vision and overcome tht: challenges. In contrary, for the recent years civil servants were heavily subjected to criticisms as their work ethics very often associated with poor performance. Therefore, this study is intended to look at the presence of ethical elements and the extent of its relationship on work performance. This study has been carried out at one of government agencies, namely Penang Regional Development Authority (PERDA). METHOD. Data is collected through questionnaires among the support group I and 2 of PERDA. The questionnaire is adapted from Rokeach Value Survey (Modified version), Awareness on Code of Ethics (20 I 0), Ethical Leadership Questionnaire (20 1 0) and Work Performance Survey (200 1 ). ANALYSIS. The researcher examines the relationships of Personal Values (IV 1 ), Awareness on Codes of Work Ethics (IV 2) and Ethical Leadership (IV 3) towards Work Performance (DV). The Statistical Package for Social Science (version 20) has been used to ease and systemize the data analysis process.